Transformasi Manajemen Pendidikan Di Wilayah Pesisir Inhil: Analisis Dinamika Sosial-Ekonomi Masyarakat - Indra Putra, Edi Susrianto; Ahmad; Khairuddin, Khairuddin; Muthalib, A.; Hasnawati, Hasnawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Indragiri (UNISI), 2025)
This study reveals that changes in education governance in the coastal areas of Indragiri Hilir Regency occur substantially through the implementation of participatory and collaborative models involving educational institutions, communities, and local government. This paradigm shift is characterized by three key innovations: modification of academic schedules adapted to the economic cycles of fishermen and coconut cultivation; integration of local maritime wisdom values into the curricular system; and strengthening of synergy among educational institutions, students' families, and coastal communities. The main driving elements include increased community expectations toward education, livelihood diversification, and expansion of digital access in coastal areas. Constraints encountered include limited educational facilities, volatility of fishermen families' income, and high student mobility affecting learning continuity. These changes yield positive impacts on improving academic participation, curriculum relevance to local realities, and efficiency of educational institution management. Nevertheless, the sustainability of this transformation requires education policies responsive to the socio-economic characteristics of the coastal communities of Indragiri Hilir.